2019
DOI: 10.1136/rapm-2018-100089
|View full text |Cite
|
Sign up to set email alerts
|

Systemic dexmedetomidine is not as efficient as perineural dexmedetomidine in prolonging an ulnar nerve block

Abstract: BackgroundWe tested the joint hypotheses that both perineural and systemic dexmedetomidine prolong the duration of an ulnar nerve block (UNB) compared with ropivacaine alone and that systemic dexmedetomidine is noninferior compared with perineural dexmedetomidine in block prolongation.MethodsWe performed bilateral UNBs in 22 healthy volunteers on two separate days. On the first day, each arm was randomized to either 4 mL ropivacaine 5 mg/mL+1 mL dexmedetomidine 100 µg/mL (Perineural) or 4 mL ropivacaine 5 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…As an adjuvant medication, dexmedetomidine has been used by different routes to prolong the duration of local anaesthetics. It has been shown to prolong the duration of regional blocks when administered perineurally 25,26 and shown to prolong the duration of subarachnoid block when administered via the intrathecal route, 2,[27][28][29] suggesting both peripheral and central mechanisms of action for dexmedetomidine. It has high selectivity towards α2-adrenergic receptors 30 acting at the presynaptic C-fibers, postsynaptic dorsal horn neurons and locus ceruleus of the brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…As an adjuvant medication, dexmedetomidine has been used by different routes to prolong the duration of local anaesthetics. It has been shown to prolong the duration of regional blocks when administered perineurally 25,26 and shown to prolong the duration of subarachnoid block when administered via the intrathecal route, 2,[27][28][29] suggesting both peripheral and central mechanisms of action for dexmedetomidine. It has high selectivity towards α2-adrenergic receptors 30 acting at the presynaptic C-fibers, postsynaptic dorsal horn neurons and locus ceruleus of the brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…Brummett et al [ 8 ] showed that dexmedetomidine could increase the action time and improve the potency of ropivacaine in rats. Andersen et al [ 10 ] found that dexmedetomidine could increase the action time of ulnar nerve block. Andersen et al [ 14 ] also reported that dexmedetomidine could extend the duration of nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural adjuvant of local anesthetics is a useful technique to address this problem [ 7 ]. Previous studies found that dexmedetomidine can improve the potency of local anesthetics, while sparing nerve injury [ 8 10 ]. However, whether the quantity of local anesthetic for adductor canal block can be reduced by dexmedetomidine has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Метааналіз переглянув 14 клінічних досліджень із 848 пацієнтами для порівняння периневрального дексмедетомідину проти клонідину. Було встановлено, що дексмедетомідин подовжував тривалість сенсорного та моторного блоку [60,61]. Ефект дексмедетомідину в сім разів перевищує ефект клонідину [58,59].…”
Section: оглядunclassified
“…порівняло периневральне введення з внутрішньовенним. Хоча було виявлено, що обидва шляхи дексмедетомідину подовжують тривалість ропівакаїну, периневральний шлях введення виявився ефективнішим, ніж при системному застосуванні [61].…”
Section: оглядunclassified